Estudo comparativo do desempenho de diferentes membranas oclusivas de Látex Natural no reparo ósseo - Morais, Rubia Carolina Nobre; Marques, Leonardo; Holgado, Leandro Andrade; Floriano, Juliana Ferreira [UNESP]; Saraiva, Patrícia; Graeff, Carlos Frederico de Oliveira [UNESP]; Kinoshita, Angela Mitie Otta (My University, 2012)
Introduction: In dentistry, alveolar bone resorption is a limiting factor in the well being of individuals directly interfering in the stomatognathic system, causing problems in the context of overall health. Aiming to promote biological methods that can stimulate bone regeneration, several biomimetic strategies have been developed by the use of diverse materials possible to the bone matrix, culminating in the development of techniques that promote such repair. Objective: This work is a comparative study of the performance of films made with latex as occlusive membrane for Guided Bone Regeneration (GBR) procedure in three preparations: Latex preserved in ammonia, produced by Latex rubber clones IAN873 and PR255 polymerized immediately after collection and without use ammonia as a preservative. Methods: Sixty Wistar rats were randomly divided into 4 groups of 15 animals in which bone defects of critical size (8mm diameter) were made surgically in the skull. Group A was treated by GBR through the membrane latex preserved with ammonia, Group B received the membrane made of latex from IAN873, Group C, the membrane clone PR255 and group D was not treated by GBR. After a period of 7, 15 and 50 days, 5 animals from each group were euthanized, and specimens containing bone defect collected for microscopic examination (descriptive histology and histomorphometry). Results: The results showed that after 50 days there was bone formation in higher proportions in group D (p <0.05, ANOVA followed by Tukey), suggesting that further experiments should be conducted to conclude about the presence of ammonia and the influence of kind of rubber. Conclusion: GOR is a procedure proven effective in the treatment of bone defects. Therefore, further experiments should be conducted to reach a conclusion regarding the presence of ammonia in the latex composition for the manufacture of membranes, as well as the difference induced by the species of rubber.

Introdução: Na odontologia, a reabsorção óssea alveolar é fator limitante no bem estar dos indivíduos interferindo diretamente no sistema estomatognático, acarretando problemas no âmbito de saú- de em geral. Com o objetivo de promover modalidades biológicas que possam estimular a regeneração óssea, várias estratégias biomiméticas têm sido desenvolvidas recorrendo à utilização dos mais diversos materiais possíveis à matriz óssea, culminando com o desenvolvimento de técnicas que promovam tal reparo. Objetivo: Este trabalho consiste no estudo comparativo do desempenho de filmes confeccionados com Látex como membrana oclusiva em procedimento de Regeneração Óssea Guiada (ROG) em 3 preparações: Lá- tex preservado em amônia, Látex produzidos por seringueiras dos clones IAN873 e PR255 polimerizados logo após a coleta e sem uso de amônia como conservante. Métodos: Foram utilizados 60 ratos Wistar, divididos randomicamente em 4 grupos de 15 animais, nos quais defeitos ósseos de tamanho crítico (8mm de diâmetro) foram confeccionados cirurgicamente na calvária. O Grupo A foi tratado por ROG através da membrana de Látex preservada em amônia, o Grupo B recebeu a membrana do clone IAN873, o Grupo C, a membrana do clone PR255 e o grupo D, não foi tratado por ROG. Após o período de 7, 15 e 50 dias, 5 animais de cada grupo foram eutanasiados, e as peças contendo o defeito ósseo coletadas para análise microscópica (histológica descritiva e histomorfometria). Resultados: Os resultados demonstraram que após 50 dias, houve formação óssea em maiores proporções no grupo D (p<0.05, ANOVA seguido de Tukey), sugerindo que novos experimentos devem ser realizados para se concluir a respeito da presença da amônia e a influência da espécie de seringueira. Conclusão: A ROG é um procedimento comprovadamente eficaz no tratamento de defeitos ósseos. Sendo assim, novos experimentos devem ser realizados para se concluir a respeito da presença da amônia na composição do látex para fabricação de membranas, bem como na diferença induzida pela espécie de seringueira.
A comparative study on the performance of different occlusive natural latex membranes in bone repair
Keywords: Guided bone regeneration; Membrane occlusive latex; Regeneração óssea guiada; Membrana oclusiva; Látex